The Apostles' Creed : all you need to believe - Cole, C. Donald; Bell, James S.; Cole, C. Donald (Chicago : Moody Press, 1998)
IN "All you need to believe" Donald Cole shows that the Apostles' Creed is far more than a series of doctrinal affirmations to be recited on Sunday mornings. In fact, Cole asserts that the Creed is such a profound compendium of Christian truth that carefully studying its components will enrich your spiritual life while adding precision and depth to your understanding of the faith.
Belief in God is personal -- "I believe in God" -- "I believe in God the father" -- "I believe in God the father almighty" -- "I believe in Jesus Christ" -- "I believe in Jesus Christ, his only son" -- "I believe in Jesus Christ, our Lord" -- "Born of the virgin Mary" -- "Suffered under Pontius Pilate" -- "I believe in Jesus Christ ... crucified" -- "I believe in Jesus Christ ... dead" -- The riches of Christ's death -- "I believe in Jesus Christ ... buried" -- "He descended into hell" -- "The third day he rose from the dead" -- "He ascended into heaven" -- "And sitteth on the right hand of God" -- "From thence he shall come" -- "To judge the quick and the dead" -- "I believe in the holy ghost" -- "The Holy Catholic Church" -- "The communion of saints" -- "The forgiveness of sins" -- "The resurrection of the body" -- "And life everlasting."
Revised edition of: "I believe-- ". c1983.
"Review and study guide" by James S. Bell, Jr.
Includes bibliographical references.
Keywords: Apostles' Creed; Theology, Doctrinal -- Popular works